Industrial Aid for Spain Committee (extract of letter from Blackpool Trades Council)
1938-05-26 036-0008-002 Trades Union Congress General Council. CORRESPONDENCE. Extract from letter sent to SECRETARY'S (File 12.1) Department. Name of Sender...................BLACKPOOL TRADES COUNCIL. Address MR. P. WILLIS, TRADES HALL, 7, CHADWICK STREET, BLACKPOOL. Date...............................26th MAY, 1938. Subject INDUSTRIAL AID FOR SPAIN COMMITTEE. I should be pleased to know if you deem the Industrial Aid for Spain Committee to be Proscribed as the address indicates it should be. [SEE OVER FOR CONTINUATION. 292/946/36/8(ii)